Influence of Homoepitaxial Layer Thickness on Flatness and Chemical Mechanical Planarization Induced Scratches of 4H-Silicon Carbide Epi-Wafers - Chi-Hsiang Hsieh; Chiao-Yang Cheng; Yi-Kai Hsiao; Zi-Hao Wang; Chang-Ching Tu; Chao-Chang Arthur Chen; Po-Tsung Lee; Hao-Chung Kuo (Micromachines)
The integration of thick homoepitaxial layers on silicon carbide (SiC) substrates is critical for enabling high-voltage power devices, yet it remains challenged by substrate surface quality and wafer geometry evolution. This study investigates the relationship between substrate preparation—particularly chemical mechanical planarization (CMP)—and the impact on wafer bow, total thickness variation (TTV), local thickness variation (LTV), and defect propagation during epitaxial growth. Seven 150 mm, 4° off-axis, prime-grade 4H-SiC substrates from a single ingot were processed under high-volume manufacturing (HVM) conditions and grown with epitaxial layers ranging from 12 μm to 100 μm. Metrology revealed a strong correlation between increasing epitaxial thickness and geometric deformation, especially beyond 31 μm. Despite initial surface scratches from CMP, hydrogen etching and buffer layer deposition significantly mitigated scratch propagation, as confirmed through defect mapping and SEM/FIB analysis. These findings provide a deeper understanding of the substrate-to-epitaxy integration process and offer pathways to improve manufacturability and yield in thick-epilayer SiC device fabrication.